Pelaksanaan Akad Mudharabah Pada Pembiayaan Produktif Wirausaha IB Hasanah ( Studi Pada BNI Syariah Kantor Cabang Yogyakarta) - , Felix Parasian Sinurat, Yulkarnain Harahab, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Research on the implementation of mudharabah covenant on financing productive entrepreneurial IB HASANAH (study in BNI SYARIAH branch office of Yogyakarta) aims to know 1) the execution of the contract on financing the entrepreneurial mudharabah IB Hasanah in BNI Syariah branch office of Yogyakarta and 2) to know the position of collateral in financing entrepreneurial IB Hasanah. Research methods of the implementation of mudharabah covenant on financing productive entrepreneurial IB HASANAH (study in BNI SYARIAH branch office of Yogyakarta) is an empirical juridical research, the research by way of reviewing the terms of the applicable legislation and also materials pertaining to materials related to research topics as secondary data primary data to support that by looking at the fact that occurred on their implementation in Bank BNI Syariah branche Yogyakarta. Research results can be presented that 1) the execution of the covenant mudharabah in financing entrepreneurial IB Hasanah in BNI Syariah Yogyakarta branch are basically already meet the applicable rules ( regulations of Fatwa DSN MUI and regulation of Indonesia Bank) and meets the Islamic principles 2) Collateral/guarantee of it serves as prevention of moral hazard or to prevent the customer who is cheating or using Fund financing for activities outside of the activities agreed in the contract.